PROPORSI ANGGARAN PROGRAM PERBAIKAN GIZI DI TINGKAT KABUPATEN/KOTA DALAM TAHUN 2003-2005 - Siti Sundari (PERSATUAN AHLI GIZI INDONESIA, 2007)
PROPORTION OF DISTRICT ALLOCATED BUDGET FOR NUTRITION IMPROVEMENT PROGRAM IN 2003-2005The 2004 Indonesian Households survey indicated that Nutritional status of the Indonesian’sunderfives had not shown positive improvement since 2000 -2005. Factors influence thatconditions among others, were less funds allocated for nutrition programs, lack of coordinationbetween sectors and within programs and lack of personnel motivation to enhance nutritionservices.This study using cross-sectional design was carried out at 6 Districts during the year 2006 andaims to analise the proportion of DHO allocated for Nutrition improvement program during the year2003-2005. The data was analysed descriptively using Excell program.The results showed that the proportion of Nutrition Program Budget was relatively equal everyyear, with the exception of higher proportion in 2003 and was second highest compare to otherDHO program’s budget. The type of activities carried out were relatively similar every yearincluding the distribution of meals to Posyandu and schools. There were some contribution madeby other units within the DHO to improve nutrional status of the underfives. The success ofnutrition services was not achieved without close coordination and support from other sectors,therefore it is important to prioritize activities and budget allocation within the related programsKeywords: nutrition program, budget, district